PLANT–SOIL–MICROBE INTERACTIONS REVISITED: MECHANISTIC INSIGHTS FROM BIOMOLECULAR AND ECOLOGICAL INTEGRATION - Jihoon, Park; Siregar, Adelina; Tanaka, Kaito; Davis, Michael (Research of Scientia Naturalis, 2026)
Plant–soil–microbe interactions underpin nutrient cycling, ecosystem productivity, and resilience under environmental change. Despite advances in rhizosphere ecology and molecular biology, integration between biomolecular processes and ecosystem-level dynamics remains fragmented. This study aims to develop and empirically validate a mechanistic framework linking gene expression, metabolite exchange, microbial functional traits, and ecological outcomes across controlled and field contexts. A multi-scale design combined greenhouse factorial experiments with field validation, integrating metagenomics, metatranscriptomics, metabolomics, soil nutrient assays, and ecological network modeling. Structural equation modeling and multivariate analyses were applied to identify causal pathways among root exudation, microbial functional gene abundance, nutrient availability, and plant biomass. Results demonstrate that functional gene abundance (? = 0.46, p < 0.001) and root metabolite diversity (? = 0.39, p < 0.01) significantly predict plant productivity, while network analysis identifies organic acids and nitrogen-fixing taxa as keystone interaction nodes. Drought treatments induced coordinated upregulation of stress-response genes and metabolite adjustments, partially buffering productivity losses. The study concludes that rhizosphere resilience emerges from tightly coupled biomolecular and ecological feedback mechanisms. Integrative multi-omics combined with ecological modeling enhances predictive understanding of ecosystem function under environmental variability.